Simplificarlo? (a + 3) ³ + (a-3) ³

Respuesta

#color(magenta)(=>18a^2+27#

#color(magenta)(=>9(2a^2+3)#

Explicación:

Usando las identidades:

#color(red)((a+b)^3= a^3+3a^2b+3ab^2+b^3#

#color(red)((a-b)^3=a^3-3a^2b+3ab^2-b^3#
image.slidesharecdn.com
Tenemos: #(a+3)^3+(a-3)^3#

#=>(a^3+3a^2*3+3a(3)^2+(3)^3)-(a^3-3a^2*3+3a(3)^2-(3)^3)#

#=>cancel(a^3)+9a^2+cancel(3a*9)+27-cancel(a^3)+9a^2-cancel(3a*9)+27#

#color(magenta)(=>18a^2+27#

#color(magenta)(=>9(2a^2+3)#

~ ¡Espero que esto ayude! 🙂


Deja un comentario